Different coupling mechanisms for a novel modular plate in acetabular fractures—a comparison using a laparoscopic model - Menger, Maximilian M.; Herath, Steven C.; Ellmerer, Andreas E.; Trulson, Alexander; Hoßfeld, Max; Leis, Artur; Ollig, Annika; Histing, Tina; Küper, Markus A.; Audretsch, Christof K. (Frontiers in Surgery, 2024)
Acetabular fractures are among the most challenging injuries in traumatology. The complex anatomy usually requires extensive surgical approaches baring the risk for iatrogenic damage to surrounding neurovascular structures. As a viable alternative, minimally invasive endoscopic techniques have emerged during the recent years. This paper reports on the feasibility of different coupling mechanisms for a novel suprapectineal plate especially designed for minimally invasive acetabular surgery. A total number of 34 participants contributed to the present study, who differed in their arthroscopic and surgical experience. A laparoscopic model was used to compare four different coupling mechanisms by the number of failed attempts, the time required for plate fixation, the influence of surgical experience as well as the learning success for each individual coupling mechanism. Moreover, the feasibility of each mechanism was evaluated by a questionnaire.The results demonstrate that plates employing grooved and pressure-sliding coupling mechanisms exhibit fewer failed attempts and reduce trial times, especially in contrast to sole sliding mechanisms. Furthermore, our study revealed that proficiency in endoscopic procedures significantly influenced the outcome. Notably, the subjective evaluation of the participants show that the pressure base and pressure-slide base plate designs are the most supportive and feasible designs. In summary, the present study evaluates for the firsttime different plate and coupling designs for minimal-invasive surgery, indicating a superior feasibility for plates with a grooved and pressure-sliding mechanism.